2018
DOI: 10.1183/13993003.00897-2018
|View full text |Cite
|
Sign up to set email alerts
|

Safety of biweekly α1-antitrypsin treatment in the RAPID programme

Abstract: α 1 -antitrypsin (α 1 -AT) deficiency is a hereditary disorder characterised by an abnormally low concentration of functional α 1 -AT in blood and tissues [1]. The primary role of α 1 -AT is to protect elastin-containing tissues, most notably the lung, against the destructive activity of proteolytic enzymes [2]. Patients with severe α 1 -AT deficiency present with serum α 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…In the RAPID clinical trial program, a subgroup of patients received bi-weekly infusions at the discretion of the treating physician to cover periods where they were unable to attend the clinic, eg, during vacations. 59 Overall, there were 933 biweekly infusions during the RAPID clinical trial program, and results showed similar rates, temporal distribution and severity of adverse events between weekly dosing with 60 mg/kg and bi-weekly dosing with 120 mg/kg AAT. 59 Therefore, given the favorable pharmacokinetic and safety profiles of bi-weekly dosing, and the willingness of AATD experts to utilize alternative dosing strategies, there is an increasingly strong rationale for the implementation of extended-interval dosing when required.…”
Section: Alternative Dosing Regimens For Aat Therapymentioning
confidence: 86%
See 1 more Smart Citation
“…In the RAPID clinical trial program, a subgroup of patients received bi-weekly infusions at the discretion of the treating physician to cover periods where they were unable to attend the clinic, eg, during vacations. 59 Overall, there were 933 biweekly infusions during the RAPID clinical trial program, and results showed similar rates, temporal distribution and severity of adverse events between weekly dosing with 60 mg/kg and bi-weekly dosing with 120 mg/kg AAT. 59 Therefore, given the favorable pharmacokinetic and safety profiles of bi-weekly dosing, and the willingness of AATD experts to utilize alternative dosing strategies, there is an increasingly strong rationale for the implementation of extended-interval dosing when required.…”
Section: Alternative Dosing Regimens For Aat Therapymentioning
confidence: 86%
“…59 Overall, there were 933 biweekly infusions during the RAPID clinical trial program, and results showed similar rates, temporal distribution and severity of adverse events between weekly dosing with 60 mg/kg and bi-weekly dosing with 120 mg/kg AAT. 59 Therefore, given the favorable pharmacokinetic and safety profiles of bi-weekly dosing, and the willingness of AATD experts to utilize alternative dosing strategies, there is an increasingly strong rationale for the implementation of extended-interval dosing when required. However, the standard dose remains the preferred choice of treatment as there are no specific efficacy data related to the 120 mg/kg biweekly dose and no data on the impact of differing trough levels between weekly and bi-weekly dosing on the efficacy of treatment.…”
Section: Alternative Dosing Regimens For Aat Therapymentioning
confidence: 86%
“…Double dosing was found to be effective at further reducing the level of serine proteases in both the airway and circulation, reducing elastin degradation, and diminishing airway inflammation when compared to standard dose therapy [ 168 , 169 ]. The RAPID Programme also demonstrated that biweekly dosing with 120 mg/kg of AAT is a safe, well tolerated and a convenient alternative to the dosing regimen currently recommended by the FDA [ 170 ]. The SPARTA trial is currently ongoing in a number of European countries to further explore the efficacy and safety of AAT in subjects with pulmonary emphysema due to AATD (NCT01983241).…”
Section: Aat Augmentation Therapymentioning
confidence: 99%
“…Alternative dosing strategies such as bi-weekly infusion of AAT therapy have been trialed 10,72 and offer favorable pharmacokinetic and tolerability profiles. 10,73 Certainly, as future data concerning dose optimization and dosage interval become available, the possibility of implementing extended-interval dosages of AAT therapy may enhance the attractiveness of self-administration therapy in patients with AATD in the years to come.…”
Section: Future Perspectives In Aatdmentioning
confidence: 99%